Synonymitis - Brink, Lars (Nordiske Studier i Leksikografi, 2018)
I try to show that there are far too many (alleged) equivalents per mean-ing variant in our bilingual dictionaries, in other words, (alleged) syno-nyms. I clarify the concepts of ’equivalent’, ’false synonyms’, ’genuine synonyms’, and ’maximal synonyms’, and state that, generally, our users only need one equivalent, the best, and that more than one is pedagogi-cally and economically harmful. The L1 speaker only needs one expres-sion for his concrete translation. He does not speak in synonyms (“my steed and horse”). The passive L2 speaker and the active L2 speaker only want to understand. One equivalent will suffice. They do not need to be informed of alternative expressions in their own mother tongue. Later, I sketch where it is useful to give several equivalents. And in the end I seek to answer why the one word ideal is not as popular as it ought to be.